The effect of toothpaste used as a composite polishing paste on the surface roughness of microhybrid composite resin - Mirasol, April A.
Polishing composite restorations are important to reduce plaque accumulation, gingival irritation and wear on the opposing dentition; to prevent recurrent caries; to allow food to glide freely along the embrasures and occlusal surfaces during mastification; and for esthetics. All polishing systems contain abrasives in order to provide a smoother surface finish and luster or gloss on composite restorations. It is given that toothpastes also contain abrasives which aids in plaque removal during toothbrushing. Objectives: To determine the effectiveness of Crest Regular toothpastes and Sensodyne Extra Whitening toothpastes in polishing microhybrid composite resin restoration by comparing it against Enhance Prisma Gloss polishing paste. Methodology: Fifteen (15) microhybrid composite resin blocks were finished using white stone composite trimmer. Using a Rugosimetre rt60 Andilog, the surface roughness before polishing (BRa) was measured. Using Fishbowl Technique, 5 finished test samples were randomly assigned to each of the 3 paste. The samples were polished for 60 seconds using a rubber cup attached to a low speed handpiece with a constant torque, speed and pressure. After polishing, the surface roughness (ARa) was measured using the same procedure protocol as in the BRa. Preparation of the sample, finishing and polishing were carried out by a single operator to reduce variability. Surface roughness was measured at the Length Standard Section of the National Metrology Laboratory Department of Science and Technology. Result: There was a decrease in surface roughness (Ra) values after polishing of the microhybrid composite resin blocks for the 3 groups. Data analyzed using One Way ANOVA (p>0.05) revealed that there no significant differences in the surface roughness of the composite restoration when polished using the 3 pastes. Conclusion: There is no significant difference in the surface roughness of microhybrid composite resins polished with Crest Regular Toothpaste, Sensodyne Extra Whitening Toothpaste and Enhance Prisma Gloss.